PEMBERIAN RANGKUMAN DALAM PROSES BELAJAR MENGAJAR - Hamsu Abdul Gani (LPMPP Universitas Negeri Yogyakarta, 2004)
One factorthat can influence learning achievement is the quality ofthe teaching-learning process designed by the teacher and implemented in class. To improve that quality, the teacher should increase students' active involvement in th,at process. One way to encourage students to be actively involved in it is providing them with a resume. The fimction ofaresume provided as a strategy oforganizing the teaching is to provide briefstatements about the main ideas ofthe contents ofthe teaching material being learned, together with easily remembered examples to refer to. The facts show that very many students are still low in level in their learning achievement. One strategy to remedy the situation is providing a resume. Four important points to consider in providing a resume in the teaching-learning process are information processing, cognitive structure, schemata, and the process ofmemorization. The resume will cause the contents ofthe teaching material to become more immediately meaningful to students. The main ideas slated in the resume can more easily guide students to the contents to be learned. In applying the concept of meaningful learning, cognitive structure and items of new knowledge play very important parts. Cognitive structure refers to all Imowledge already possessed by students as a result ofpast learning activity while items ofnew knowledge refer to those being learned by students. Key words: resume, teaching, learning process